2018
DOI: 10.1007/s00424-018-2153-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of angiotensin II type 2 receptors in the control of mitochondrial and cardiac function in angiotensin II-preconditioned rat hearts

Abstract: Angiotensin II preconditioning (APC) involves an angiotensin II type 1 receptor (AT1-R)-dependent translocation of PKCε and survival kinases to the mitochondria leading to cardioprotection after ischemia-reperfusion (IR). However, the role that mitochondrial AT1-Rs and angiotensin II type 2 receptors (AT2-Rs) play in APC is unknown. We investigated whether pretreatment of Langendorff-perfused rat hearts with losartan (L, AT1-R blocker), PD 123,319 (PD, AT2-R blocker), or their combination (L + PD) affects mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
(89 reference statements)
2
11
0
Order By: Relevance
“…These data agree with previous results (51) indicating that blockade of AT 2 R with PD123319 prevented the cardioprotection against I/R injury in valsartan-treated hearts. Altogether, these studies (66 -68) demonstrate that during APC, extracellular ANG II affects mitochondrial function through AT 2 R signaling, protecting the heart and reducing infarct size in the course of I/R injury (68). Therefore, these findings are consistent with and extend previous reports (1,98) on functional ANG II receptors in isolated mitochondria from various cell preparations.…”
Section: Mitochondrial Angiotensin Receptors and Cardioprotectionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data agree with previous results (51) indicating that blockade of AT 2 R with PD123319 prevented the cardioprotection against I/R injury in valsartan-treated hearts. Altogether, these studies (66 -68) demonstrate that during APC, extracellular ANG II affects mitochondrial function through AT 2 R signaling, protecting the heart and reducing infarct size in the course of I/R injury (68). Therefore, these findings are consistent with and extend previous reports (1,98) on functional ANG II receptors in isolated mitochondria from various cell preparations.…”
Section: Mitochondrial Angiotensin Receptors and Cardioprotectionsupporting
confidence: 89%
“…These effects of APC and losartan were prevented by PD123319. However, ARBs did not affect hearts without APC (68). These observations indicate that AT 2 R activity in APC is responsible for the beneficial effects of the AT 1 R blockade on infarct size.…”
Section: Mitochondrial Angiotensin Receptors and Cardioprotectionmentioning
confidence: 69%
See 1 more Smart Citation
“…A number of recent data support this protective view ( Nunez et al, 2014 , 2017 , 2018 ; Wanka et al, 2020 ; Wilson et al, 2016 ). Several studies have also shown that high levels of intracellular Ang II led to cell and tissue damage ( Redding et al, 2010 ; Singh et al, 2008 ).…”
Section: The Nuclear Rasmentioning
confidence: 91%
“…Extracellular Ang II influences mitochondrial function via AT2-R signaling, protecting the myocardium and decreasing infarct size in the course of I/R injury. 46…”
Section: Mitochondrial Renin-angiotensin System (Ras)mentioning
confidence: 99%